2007
DOI: 10.1002/jnr.21551
|View full text |Cite
|
Sign up to set email alerts
|

NCAM‐induced intracellular signaling revisited

Abstract: The neural cell adhesion molecule (NCAM) plays a crucial role in neuronal development, synaptic plasticity, and regeneration. NCAM works as ''smart glue'' that not only mediates cell-cell adhesion but also induces activation of a complex network of intracellular signaling cascades on homophilic or heterophilic binding. Stimulation of NCAM by homophilic interactions induces neuronal differentiation through activation of a number of signaling molecules, including the fibroblast growth factor receptor, non-recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 107 publications
0
110
0
2
Order By: Relevance
“…Additional experiments suggested that a single O-glycan attached to a serine residue at the very N terminus of NCAM7 possesses the bulk of the polysialic acid on this protein. 3 With this in mind, replacing NGKG with alanines may have made this glycan more accessible to the polySTs and enhanced polysialylation. More importantly, the observation that replacing PSSP eliminated NCAM N-glycan polysialylation, although only reducing NCAM7 O-glycan polysialylation, suggests that this sequence may play a dual role in NCAM polysialylation.…”
Section: The Ggvpi and Ngkg Sequences Do Not Play Roles In Ncam7 O-glmentioning
confidence: 99%
“…Additional experiments suggested that a single O-glycan attached to a serine residue at the very N terminus of NCAM7 possesses the bulk of the polysialic acid on this protein. 3 With this in mind, replacing NGKG with alanines may have made this glycan more accessible to the polySTs and enhanced polysialylation. More importantly, the observation that replacing PSSP eliminated NCAM N-glycan polysialylation, although only reducing NCAM7 O-glycan polysialylation, suggests that this sequence may play a dual role in NCAM polysialylation.…”
Section: The Ggvpi and Ngkg Sequences Do Not Play Roles In Ncam7 O-glmentioning
confidence: 99%
“…Even though rising evidence supports a role for astrocytes in synaptic plasticity and potentially in learning (Schummers, Yu, & Sur, 2008), a putative role for NCAM-120 in such processes has not yet been explored. However, substantial evidence supports a role for NCAM-140 (expressed both in neurons and glia) in plasticity and intracellular signaling (for a review, see Ditlevsen, Povlsen, Berezin, & Bock, 2008). For example, a constitutive association has been found between NCAM-140 and Fyn (a member of the Src family of non-receptor tyrosine kinases highly expressed in neural tissue) (Ditlevsen et al, 2008).…”
Section: Stressful Learning As a Model Of Intrinsic Stress And Ncammentioning
confidence: 99%
“…However, substantial evidence supports a role for NCAM-140 (expressed both in neurons and glia) in plasticity and intracellular signaling (for a review, see Ditlevsen, Povlsen, Berezin, & Bock, 2008). For example, a constitutive association has been found between NCAM-140 and Fyn (a member of the Src family of non-receptor tyrosine kinases highly expressed in neural tissue) (Ditlevsen et al, 2008). Interestingly, Fyn activation leads to recruitment and activation of the focal adhesion kinase (FAK), which is another non-receptor tyrosine kinase.…”
Section: Stressful Learning As a Model Of Intrinsic Stress And Ncammentioning
confidence: 99%
“…Since the PLA will only detect proteins in close proximity of each other the presence of signal indicates that NCAM and FGFR2 are co-localizing in the mouse oocyte membrane. NCAM may activate intracellular signaling pathways such as protein kinase A, protein kinase C (PKC) and the Ras-MAPK pathway (Ditlevsen et al, 2008). Although all three NCAM isoforms are redundant for embryo viability (Cremer et al, 1994) a secreted construct of the extracellular NCAM domain has been shown to result in embryonic lethality (Rabinowitz et al, 1996).…”
Section: Resultsmentioning
confidence: 99%